A plea for domestic science in the grade school - Kelly, Maude (My University, 1908)
Introduction: The novel entitled “The Breadwinners” published about 25 years ago is a social study dealing with the problems of labor. Among other points the author presents the idea that education of the laboring classes would not improve the labor situation. Subsequent development, however, shows that in this his estimate has not been justified.
Citation: Kelly, Maude. A plea for domestic science in the grade school. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Home Economics; Education; Graduating theses; Senior theses; Theses